(untitled) (Research, Society and Development, 2021)
School feeding aims to contribute to increase the nutritional conditions of students, make them stay in school, promote food education, also contribute to the improvement of the teaching-learning process and, consequently, reduce dropout and repetition rates. School feeding is a vital issue, as school feeding also adds values, such as the formation of eating habits and attitudes. This article aims to discuss the School Meals Council (CAE) in its conceptual, legal and challenges aspects in the development of the duties of the counselor. For This is a study of bibliographic review, where search sites, such as Google Scholar and SCIELO, were used, using the keywords: school meals, school feeding council. Challenges, with the research it was possible to raise the data that support this study. The main challenge is the lack of preparation and knowledge of the legislation of the National School Feeding Program (PNAE), since in practice there are no courses aimed at preparing counselors to work at the CAE, with many attributions regarding the work of the CAE directors. The challenges are still the lack of structure to hold meetings and the lack of transportation for visits to schools, which ends up hindering the CAE’s objective and consequent execution in the PNAE.